Kearifan al-Qur'an: Eksistensi, Idealitas, Realitas, normativitas dan Historitas - CHIRZIN, H. Muhammad (PILAR MEDIA, 2007)
Kearifan al-Qur'an: Eksistensi, Idealitas, Realitas, normativitas dan Historitas